If g(x) = x² , which expression is equal to g(x + 1) ?

A.) 1

B.) x² + 1

C.) x² + 2x + 1

D.) x² - x

E.) x² + x + 1

A.) 1

B.) x² + 1

C.) x² + 2x + 1

D.) x² - x

E.) x² + x + 1

g(x) = x²

g(x + 1)

= (x + 1)² {replaced the x, in g(x), with (x + 1)}

= (x + 1)(x + 1) {when squaring a binomial, multiply it by itself}

= x² + x + x + 1 {used FOIL method / distributive property}

= x² + 2x + 1 {combined like terms}

g(x + 1)

= (x + 1)² {replaced the x, in g(x), with (x + 1)}

= (x + 1)(x + 1) {when squaring a binomial, multiply it by itself}

= x² + x + x + 1 {used FOIL method / distributive property}

= x² + 2x + 1 {combined like terms}

**E.) x² + 2x + 1**__Ask Algebra House__